2001
DOI: 10.1210/jc.86.5.2191
|View full text |Cite
|
Sign up to set email alerts
|

 1- and  2-Adrenoceptor-Mediated Thermogenesis and Lipid Utilization in Obese and Lean Men

Abstract: The aim of this study was to elucidate the roles of the ␤ 1 -and the ␤ 2 -adrenoceptors in thermogenesis and lipid utilization in obesity. The ␤ 1 -adrenoceptor study was performed in 9 obese and 10 lean men and consisted of 4 30-min periods during which subjects received consecutive infusions of 0, 3, 6, and 9 g/kg fat-free mass (FFM)⅐min dobutamine. Energy expenditure, lipid oxidation, and plasma nonesterified fatty acids and glycerol concentrations increased similarly in both groups during ␤ 1 -adrenergic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 34 publications
2
50
1
Order By: Relevance
“…In summary, nonselective b-, b 1 -and b 2 -adrenoceptormediated increases in interstitial glycerol concentration and local nutritive blood flow were similar in subcutaneous abdominal adipose tissue in obese and lean men. This suggests that the diminished whole-body b-adrenoceptormediated lipolytic response, as reported earlier by our group, 3,5 is probably not for a large part explained by a blunted local adipocyte b-adrenergic sensitivity or nutritive blood flow. More likely, the impaired whole-body lipolytic response during i.v.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In summary, nonselective b-, b 1 -and b 2 -adrenoceptormediated increases in interstitial glycerol concentration and local nutritive blood flow were similar in subcutaneous abdominal adipose tissue in obese and lean men. This suggests that the diminished whole-body b-adrenoceptormediated lipolytic response, as reported earlier by our group, 3,5 is probably not for a large part explained by a blunted local adipocyte b-adrenergic sensitivity or nutritive blood flow. More likely, the impaired whole-body lipolytic response during i.v.…”
Section: Discussionsupporting
confidence: 80%
“…4 In an earlier study, we showed that this blunted b-adrenoceptor-mediated lipolytic response only occurs during selective b 2 -adrenergic stimulation, whereas b 1 -adrenoceptor-mediated increases in lipolysis are similar in obese and lean men. 5 Several mechanisms may be responsible for the impaired whole-body b-adrenoceptor-mediated lipolytic response. On the one side, adipocyte b-adrenergic sensitivity for lipolysis might be diminished.…”
Section: Introductionmentioning
confidence: 99%
“…We should emphasize that there is evidence that the increase in metabolic rate in response to b-AR stimulation is smaller with increasing adiposity, 25,26 as may be the increase in fat oxidation, 25,27 heart rate, 8,25 and blood flow to adipose tissue. 7 Chronically elevated sympathetic activity with increasing total 12,28,29 and abdominal 4,30 adiposity may reduce b-AR responsiveness due to desensitization of the b-AR signaling pathway [9][10][11] and explain these previous observations.…”
Section: Discussionmentioning
confidence: 95%
“…When ANOVA for group was significant, unpaired Student's t-test was performed. 4 The SPSS 7.5 version for WINDOWS was used for the statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Furthermore, it has been suggested that ADRB2 is responsible for the impaired effects in thermogenesis, lipid oxidation and lipolysis in the obese in vivo. 4 Several polymorphisms have been described 5 both in the coding region of the ADRB2 gene (Arg16Gly, Gln27Gln, Thr164Ile) and in the 5 0 leader cistron (Cys19Arg), that result in significantly changed functions of this receptor. 6 -8 Indeed, polymorphisms in the coding region showed an ADRB2 functional impairment in recombinant cells.…”
Section: Introductionmentioning
confidence: 99%